Transfers of lower quality embryos based on morphological appearance result in appreciable live birth rates: a Canadian center's experience - Ingrid Lai, M.D; Michael Neal, M.Sc; Nicole Gervais, M.A; Shilpa Amin, M.D; Evan Taerk, M.D; Mehrnoosh Faghih, M.D (Elsevier, 2020)
Objective: To determine the reproductive outcomes resulting from transfer of lower-grade blastocysts to support the practice of cryopreserving and transferring lower-grade embryos. Design: Retrospective chart review. Setting: Single infertility center. Patient(s): Women who have undergone a fresh (n = 570) or frozen (n = 885) transfer of a single blastocyst embryo between December 2013 and December 2018. Intervention(s): None. Main Outcome Measure(s): The primary outcome was live birth rate. The secondary outcomes included implantation rate, ongoing pregnancy rate, associations with inner cell mass (ICM) and trophectoderm epithelium (TE) grades determined by morphological assessment, and antenatal/perinatal complications. Results: Reproductive outcomes directly correlated with embryo quality. Transfers of AA embryos resulted in a 41.4% live birth rate compared to 31.1% for BB embryos and 13.3% for CC embryos. The TE grade was significantly associated with the live birth rate. Embryos with a TE grade of "B" had an odds ratio of 0.677 and embryos with a TE grade of "C" had an odds ratio of 0.394 compared to embryos with a TE grade of "A" for live birth. Conclusion: Embryos with a TE "C" grade should be considered for transfer and cryopreservation, as they are shown to result in appreciable live birth rates. Such treatment should involve a thorough discussion with patients, however, as these live birth rates are significantly lower than those associated with higher-grade embryos.